Local Government Actions in Disputes over the Installation of Hawear in Public Facilities - Baranyanan, Soeleman Djaiz; Tita, Heillen Martha Yosephine (PAMALI: Pattimura Magister Law Review, 2025)
Introduction: The diversity of the Indonesian nation is a reality, even this diversity is a wealth as a gift from God who has stated that humans were created in groups so that they can get to know each other. This article discusses the actions of the local government in resolving the problem of installing hawear, a traditional symbol of the Kei community, which often clashes with the interests of building public facilitie.Purposes of the Research: This study aims to analyze the role and actions of local governments in resolving disputes over the installation of hawear, with a focus on the mediation process and the implementation of related policies.Methods of the Research: This study uses empirical juridical research methods with legal materials used in research are primary, secondary and tertiary with the use of literature study techniques in the form of applicable legal regulations, scientific works and several other literature.Results Main Findings of the Research: In the Kei Islands, Maluku, hawear serves as a marker of the boundaries of sacred customary territories according to Larvul Ngabal customary law. However, along with the development of the times and the need for infrastructure development, the installation of hawear often triggers conflicts between indigenous peoples and the government. The dispute over the installation of hawear (customary boundary signs) on public facilities in the Kei Islands, Maluku, has become a complex issue related to the duality of the government system, namely between Customary Villages and Administrative Villages. This conflict was triggered by differences of opinion regarding customary authority and the authority of local governments in determining territorial boundaries and public land use. This study explores the role of local governments in handling these disputes through mediation, negotiation, and harmonization approaches between customary law and positive law.